Deepened winter snow increases stem growth and alters stem δ13C and δ15N in evergreen dwarf shrub Cassiope tetragona in high-arctic Svalbard tundra. (14th April 2015) - Blok, Daan; Weijers, Stef; Welker, Jeffrey M; Cooper, Elisabeth J; Michelsen, Anders; Löffler, Jörg; Elberling, Bo
Abstract: Deeper winter snow is hypothesized to favor shrub growth and may partly explain the shrub expansion observed in many parts of the arctic during the last decades, potentially triggering biophysical feedbacks including regional warming and permafrost thawing. We experimentally tested the effects of winter snow depth on shrub growth and ecophysiology by measuring stem length and stem hydrogen ( δ 2 H), carbon ( δ 13 C), nitrogen ( δ 15 N) and oxygen ( δ 18 O) isotopic composition of the circumarctic evergreen dwarf shrub Cassiope tetragona growing in high-arctic Svalbard, Norway. Measurements were carried out on C. tetragona individuals sampled from three tundra sites, each representing a distinct moisture regime (dry heath, meadow, moist meadow). Individuals were sampled along gradients of experimentally manipulated winter snow depths in a six-year old snow fence experiment: in ambient ( c . 20 cm), medium ( c . 100 cm), and deep snow ( c . 150 cm) plots. The deep-snow treatment consistently and significantly increased C. tetragona growth during the 2008–2011 manipulation period compared to growth in ambient-snow plots. Stem δ 15 N and stem N concentration values were significantly higher in deep-snow individuals compared to individuals growing in ambient-snow plots during the course of the experiment, suggesting that soil N-availability was increased in deep-snow plots as a result of increased soil winter N mineralization. Although inter-annual growing season-precipitation δ 2 H and stem δ 2 H records closely matched, snow depth did not change stem δ 2 H or δ 18 O, suggesting that water source usage by C. tetragona was unaltered. Instead, the deep insulating snowpack may have protected C. tetragona shrubs against frost damage, potentially compensating the detrimental effects of a shortened growing season and associated phenological delay on growth. Our findings suggest that an increase in winter precipitation in the High Arctic, as predicted by climate models, has the potential to alter the growth and ecophysiology of evergreen shrub C. tetragona through changes in plant mineral nutrition and frost damage protection.